The Role of Supreme Court Jurisprudence in Development of Islamic Family Law in Indonesia - Arip Purkon; Ahmad Hidayat Buang; Mohd. Hafiz Jamaludin (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2022)
The development of Islamic family law is carried out in all countries where the majority of the population is Muslim. New ideas in the field of Islamic family law are generally stated in the form of legislation. In Indonesia, the final court decision in the field of Islamic family law decided with the judges of Indonesian Supreme Court. The decision of Supreme Court judge will be jurisprudence. This study aims to examine the role of Supreme Court's jurisprudence in development of Islamic family law. The research conducted was library research. This study concluded: First, Judges of the Supreme Court in the Islamic civil field have a very important role in the development of Islamic family law in Indonesia. Judges can make breakthroughs or reform the thoughts of Islamic family law as outlined in the decisions they issued. Second, decisions of Supreme Court judges that have permanent legal, fixed and final will be used as jurisprudence or references by judges in the Religious Courts.